Korczak Janusz, Makarenko Anton, Zaharenko Olexandr – Knights of Humane Pedagogy - Bida, Olena; Prokopenko, Lyudmyla (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
History does not have so many knights of pedagogy, such Teachers whom thousands of students are grateful to, whose names are carved on the tables of human memory. Yanush Korchak and Oleksandr Zaharenko are among them, they were eager to do good to the people, they gave lives for the humanity, for the happiness of everybody. The courseы of life of two prominent Teachers is discussed in the article, the professional credos of prominent teachers-humanists are singled out. We cited a famous French writer-humanist Saint-Exupery in the epigraph. In our opinion, his quotation is a professional credo of all famous teachers’ humanists. Besides, these Fox’s words (the character from “Little Prince”) appear to be the combined motto of several teachers humanists, namely: a Polish educator Yanush Korchak who was announced an Educator of 1979 by UNESCO; a Ukrainian pedagogue Anton Makarenko, announced an Educator of 2008 by UNESCO; a prominent educator and a great teacher-humanist Olexandr Zaharenko, an academician from Sahnivka, a small village in Cherkasy region.